A review on digital transformation in healthcare waste management: Applications, research trends and implications - Sharma V.; Jamwal A.; Agrawal R.; Pratap S. (My University, 2025)
At present, both emerging and developed economies have faced the challenge of higher healthcare waste generation. Developed countries are using these technologies to manage healthcare waste and cope with the challenge. Emerging economies are still struggling to understand and implement digital technologies in healthcare waste management, posing a danger to partners handling toxic and hazardous waste. The proper handling of healthcare waste is essential for social and environmental sustainability. Digital technologies that drive digital transformation in the healthcare sector impact the traditional way of managing healthcare waste. Digital technologies include artificial intelligence, blockchain, the Internet of Things, sensors, data analytics and radio frequency identification. These technologies can potentially address vehicle route planning and scheduling problems, resource optimisation, real-time tracking and the visibility of healthcare waste management. Apart from economic and environmental concerns, the operational workforce also takes care of societal well-being and implements waste management strategies and policies. Past research has focused on integrating blockchain technology to enhance traceability and transparency in waste collection and disposal activities. However, the application and impact of these technologies for managing different operations of healthcare management with sustainability is a gap bridged by the present study. This study adopts a systematic literature review to identify research trends, applications and implications of digital transformation. It proposes a digital technology-driven framework for healthcare waste management for further research. © The Author(s) 2024.